2014
DOI: 10.1016/j.jcin.2014.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Periprocedural Complications and Long-Term Outcome After Alcohol Septal Ablation Versus Surgical Myectomy in Hypertrophic Obstructive Cardiomyopathy

Abstract: Survival and clinical outcome were good and comparable after ASA and myectomy. More periprocedural complications and longer duration of hospital stay after myectomy were offset by higher gradients after ASA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(36 citation statements)
references
References 18 publications
4
32
0
Order By: Relevance
“…Sorajja et al reported comparable survival between ASA and surgical myectomy, without an increased risk of sudden death; however, the reintervention rate for ASA was significantly higher (43). Similar results were reported by Liebregts et al in a recent meta-analysis as well as other single-center studies (55,56). Conversely, Cate et al reported a five-fold increase in the incidence of cardiac death and arrhythmic complications after ASA as compared to myectomy (50), and Vriesendorp et al still reported a slight increase in sudden cardiac death after ASA when compared to myectomy (57).…”
Section: Ablation Versus Myectomysupporting
confidence: 66%
“…Sorajja et al reported comparable survival between ASA and surgical myectomy, without an increased risk of sudden death; however, the reintervention rate for ASA was significantly higher (43). Similar results were reported by Liebregts et al in a recent meta-analysis as well as other single-center studies (55,56). Conversely, Cate et al reported a five-fold increase in the incidence of cardiac death and arrhythmic complications after ASA as compared to myectomy (50), and Vriesendorp et al still reported a slight increase in sudden cardiac death after ASA when compared to myectomy (57).…”
Section: Ablation Versus Myectomysupporting
confidence: 66%
“…When superimposing the survival curves, however, again matching for age and gender, the exact same survival of roughly 80% at 8-10 years was seen, suggesting that (I) there may be no realistic age limit to positively impact the natural history, (II) elimination of obstruction itself confers the survival benefit, and (III) scar development from ablation is not meaningfully pro-arrhythmic to outweigh this benefit (11). Since the publication of this paper, other series have also shown similar survival curves out to 10 years for both surgical myectomy and alcohol ablation, confirming these benefits (12).…”
mentioning
confidence: 52%
“…Over past decades, myectomy evolved into a comprehensive repair technique for LVOTO. Long-term survival after myectomy was equivalent to those in the age- and sex-matched background population and similar to those with nonobstructive hypertrophic cardiomyopathy among drug-refractory symptomatic HOCM patients [6,8,12,13,14]. Due to such satisfactory long-term outcomes, myectomy was considered the “gold standard therapy” for HOCM in North America and Europe [2,3,20].…”
Section: Discussionmentioning
confidence: 91%
“…Severe left ventricular hypertrophy is associated with a higher incidence of SCD [4,5]. Myocardial septal myectomy has been reported to improve both symptoms and survival [6,8,12,13,14]. However, the extent to which myectomy could have a beneficial impact upon the risk of SCD has not yet been established.…”
Section: Discussionmentioning
confidence: 99%